Comparing the Effectiveness of Paroxetine, Attention Modification Program and Combination of both on Improving Social Anxiety Symptoms - Aliasghar Asgharnejad Farid; Hassan Ashayeri; Behrooz Birashk; Hosein Khedmatgozar (Basic and Clinical Neuroscience, 2012)
Introduction: Although the effectiveness of paroxetine and Attention Modification Program has been studied separately in treating social anxiety disorder, there has been no research comparing them according to the literature. The aim of this study was to compare the effectiveness of paroxetine, Attention Modification Program (AMP) and combination of both on improving the Social Anxiety Symptoms.Methods:33 patients meeting DSM-IV-TR criteria for social anxiety disorder were randomly assigned in 3 groups: 11 in paroxetine group, 11 in AMP group and 11 in combined group. Treatment intervention was done during 8 weeks period. Social Phobia Inventory (SPIN), Beck Depression Inventory (BDI-II) and Sheehan Disability Scale (SDS) were administered before and after treatment intervention. One-way Analysis of Covariance (ANCOVA) was used to determine the differences and efficacy of treatment interventions between groups. Data analysis was done by SPSS-16 software.Results:28 participants completed the treatment period. One-way ANCOVA results showed statistically significant differences in post-treatment scores of social phobia (p=0/007), depressive symptoms (p=0.007) and daily life functioning (p=0.011) between three groups. Bonferroni correction showed that combined treatment is significantly more effective than AMP in reducing social phobia symptoms (p=0.007), depressive symptoms (p=0.022) and enhancing daily life functioning (0.019). Yet, there were no significant differences between Paroxetine and combined treatment in all post-treatment scores (p=0.890, p=1.000, p=1.000 for social phobia, depressive symptoms and daily life functioning respectively). Paroxetine showed more significant improvement of depressive symptoms (p=0.016) and enhancing daily life functioning (p=0.045) than AMP. Also, there were no significant differences between paroxetine and AMP in reducing social anxiety symptoms.Discussion:It seems that paroxetine has wider effect in reducing social anxiety symptoms, depressive symptoms and enhancing daily life functioning than AMP and adding the AMP to paroxetine does not make significant changes than medicating with paroxetine alone.